2019
DOI: 10.1002/jper.18-0564
|View full text |Cite
|
Sign up to set email alerts
|

High‐fat diet aggravates the liver disease caused by periodontitis in rats

Abstract: Background: Periodontitis is an inflammatory disease that causes periodontium and hepatic alterations. Liver disease is related to the intake of foods rich in fat and sugars (high-fat). The objective of this study was to evaluate whether a high-fat diet can aggravate the liver disease caused by ligature-induced periodontitis in rats.Methods: Twenty-one female rats were divided into three groups (n = 7 in each group): control; periodontitis (periodontitis induced with ligature) and high-fat + periodontitis (rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 40 publications
0
16
0
1
Order By: Relevance
“…Furthermore, similarly to other infectious or chronic inflammatory diseases [59], periodontal diseases might alter concentration and composition of plasma lipids and lipoproteins [60], promoting atherosclerosis and NAFLD progression. In fact, studies on different experimental periodontitis rodent models suggest that this condition led to increases in TGs [61,62] and total cholesterol and to a decrease in HDL-cholesterol [62,63]. However, Ebersole et al [64] reported an increase in serum cholesterol, but no change in TGs in a non-human primate model of ligature-induced periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, similarly to other infectious or chronic inflammatory diseases [59], periodontal diseases might alter concentration and composition of plasma lipids and lipoproteins [60], promoting atherosclerosis and NAFLD progression. In fact, studies on different experimental periodontitis rodent models suggest that this condition led to increases in TGs [61,62] and total cholesterol and to a decrease in HDL-cholesterol [62,63]. However, Ebersole et al [64] reported an increase in serum cholesterol, but no change in TGs in a non-human primate model of ligature-induced periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies also reported that ligature‐induced periodontitis in rats induced mild hepatic damage through increased malondialdehyde and decreased antioxidant glutathione production present in both the blood and liver 50,51,57,150 . Furthermore, a high‐fat or high cholesterol diet cooperatively with periodontitis enhanced intrahepatic oxidative stress, resulting in exacerbation of steatohepatitis 152,154 …”
Section: Potential Mechanisms By Which Periodontal Disease May Increase the Risk Of Nonalcoholic Fatty Liver Disease/nonalcoholic Steatohmentioning
confidence: 96%
“…Moreover, in animal models of metabolic diseases showing obesity or diabetes, periodontal inflammation and bacterial infection enhanced metabolic disorders in the liver, resulting in accelerated progression of nonalcoholic fatty liver disease. 23 , 55 , 151 , 152 , 153 , 154 Although not all mechanisms explaining the interaction between periodontal disease and metabolic diseases are known, diffusion of inflammatory mediators and reactive oxygen species from inflamed periodontal tissues into the circulation can mediate low‐grade systemic inflammation, and thereby exacerbate insulin resistance in obesity and diabetes. 155 Ishikawa et al reported that hyperglycemia promotes translocation of P. gingivalis from the oral cavity to the liver and reduces hepatic insulin‐induced glycogen biosynthesis in mice.…”
Section: Relationship Between Periodontal Disease Nonalcoholic Fatty Liver Disease/nonalcoholic Steatohepatitis and Metabolic Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…Obesity is characterized by inflammation‐related impairment of lipid and glucose metabolism in many organs (Gonzalez‐Muniesa et al, 2017), while periodontitis is manifested by inflammation‐based dysregulation of collagen and alveolar bone metabolism (Crotti et al, 2015; Franco et al, 2017). In this context, the two conditions have been interacted via impaired metabolic response in lipid (Cury et al, 2018; Zelkha et al, 2010), glucose (Martinez‐Herrera et al, 2017; Solini et al, 2019; Song et al, 2016) and bone metabolism (Dittmann et al, 2015), oxidative stress (Bullon et al, 2009) and other metabolic pathways (Andrade et al, 2019; Kuraji et al, 2018). These metabolic links between obesity and periodontitis are targeted but also limited.…”
Section: Introductionmentioning
confidence: 99%